The Bible and Crusade narrative in the twelfth century - Smith, Katherine Allen (The Boydell Press, 2020)
A new investigation into the twelfth-century accounts of the First Crusasde, showing their complex relationship with the Bible
Keywords: Bibel; Kreuzzug -- 1096-1099; Bibellektüre; Geschichtsschreibung; Rezeption; Bibelwissenschaft; Crusades; Crusades / Biblical teaching